Molecular, biological, and antigenic characterization of a Border disease virus isolated from a pig during classical swine fever surveillance in Japan. (July 2014) - Nagai, Makoto; Aoki, Hiroshi; Sakoda, Yoshihiro; Kozasa, Takashi; Tominaga-Teshima, Kaho; Mine, Junki; Abe, Yuri; Tamura, Tomokazu; Kobayashi, Tsubasa; Nishine, Kaoru; Tateishi, Kentaro; Suzuki, Yudai; et al.
In the current study, molecular, biological, and antigenic analyses were performed to characterize Border disease virus (BDV) strain FNK2012-1 isolated from a pig in 2012 in Japan. The complete genome comprises 12, 327 nucleotides (nt), including a large open reading frame of 11, 685 nt. Phylogenetic analysis revealed that FNK2012-1 was clustered into BDV genotype 1 with ovine strains. FNK2012-1 grew in porcine, bovine, and ovine primary cells and cell lines, but grew better in bovine and ovine cells than in porcine cells. Specific pathogen–free pigs inoculated with FNK2012-1 did not show any clinical signs. Noninoculated contact control pigs also did not show clinical signs and did not seroconvert. The results suggest that FNK2012-1 may be of ruminant origin and is poorly adapted to pigs. Such observations can provide important insights into evidence for infection and transmission of BDV, which may be of ruminant origin, among pigs.